Associação entre implantes odontológicos e próteses parciais removíveis: revisão de literatura - Silva, Marcos Aurélio Bomfim da; Consani, Rafael Leonardo Xediek; Oliveira, Guilherme José Pimentel Lopes de [UNESP]; Reis, José Ivo Limeira dos [UNESP]; Fontanari, Lucas Amaral; Reis, José Maurício dos Santos Nunes [UNESP] (My University, 2011)
Unilateral or bilateral distal-extension removable partial dentures present complex biomechanics. The movements in different directions, associated with the alveolar ridge shape and soft tissue resilience can lead to damaging forces on the supporting structures. The association between implants / removable partial denture aims to provide better mechanical and biological properties to the stomatognathic system. OBJECTIVE: The aim of this paper was to review the articles about the effect of implant support on distal extension removable partial dentures. LITERATURE REVIEW AND CONCLUSION: Studies have shown that this combination provides greater support, retention and stability to the prosthesis, thus limiting their approach movement toward supporting tissues and providing functional and psychological comfort to patients.

A prótese parcial removível de extremidade livre unilateral ou bilateral apresenta complexa biomecânica. Seus movimentos em diversas direções, juntamente com a forma do rebordo alveolar e a resiliência da fibromucosa, podem levar a forças danosas sobre as estruturas de suporte. A associação entre implantes e prótese parcial removível visa proporcionar melhores propriedades mecânico-biológicas ao sistema estomatognático. OBJETIVO: Realizar uma revisão de literatura e discussão quanto ao uso dessa alternativa de reabilitação. REVISÃO DE LITERATURA E CONCLUSÃO: Estudos têm evidenciado que essa associação oferece maior suporte, retenção e estabilidade às próteses, limitando seu movimento de aproximação em direção aos tecidos de suporte e propiciando conforto funcional e psicológico aos pacientes.
Association between implants and removable partial dentures: review of the literature
Keywords: Partial removable denture; Dental implant; Dental abutments; Prótese parcial removível; Implante dentário; Dente suporte